Black Phosphorous Photodetectors: Black Phosphorous/Indium Selenide Photoconductive Detector for Visible and Near‐Infrared Light with High Sensitivity (Advanced Optical Materials 12/2019). Issue 12 (18th June 2019) - Cao, Rui; Wang, Hui‐De; Guo, Zhi‐Nan; Sang, David K.; Zhang, Li‐Yuan; Xiao, Quan‐Lan; Zhang, Yu‐Peng; Fan, Dian‐Yuan; Li, Jian‐Qing; Zhang, Han
Abstract : Photodetectors based on vertically stacked indium selenide (InSe) layers on top of layered black phosphorous (BP) have been devised by Zhi‐Nan Guo, Han Zhang and co‐workers (see article number 1900020 ). These vertical‐structure photodetectors possess a wide response range from visible to near‐infrared, and they exhibit a relatively fast response and high responsivity. In addition, the environmental degradation of BP can be inhibited to a certain extent by the InSe capping.